Economic Effects of Infrastructural Development in Meerut Division - Mohan, Mayank (Journal of Commerce and Trade, 2019)
Infrastructural development is the base of economic development of a country. It has an immense importance which provides the momentum to the economic development and makes the whole economy strong. Various economically developed countries like Japan, China and South Korea established their unique identity at international level in the field of industrial development on the basis of their infrastructural development.Also Meerut Division is well developed region of Uttar Pradesh in India. It is not only the area having developed agricultural business but it is famous for tyre industry, khadi udyog, pottery industry, scissors industry, agricultural equipment industry, sports industry, transformer industry, publication industry, chemical industry, paper industry etc. and it is due to strong and developed infrastructure of this area. High employment level, fast industrialisation, expended urbanisation, increasing standard of living can be very well seen in the economic activities of this division which is due to fast development of infrastructure in this Division. Classification-JEL : A 11, N35, H54